1996
DOI: 10.1038/bjc.1996.186
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of photodynamic therapy by mitomycin C: a preclinical and clinical study

Abstract: Summary Photodynamic therapy (PDT) using Photofrin was used in combination with a hypoxic toxin (mitomycin C, MMC) to treat four patients with recurrent skin metastasis of a mammary carcinoma. In precinical experiments an additive effect was found for the combination of MMC and PDT for treating subcutaneous RIFI tumours in mice. When interstitial PDT was combined with a low dose of MMC (administered 15 min before illumination), the Photofrin dose or light dose could be reduced by a factor of 2 in order to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…The same authors have also treated four patients with breast metastases to the skin. They were able to achieve similar responses in those tumours treated with MMC followed by photodynamic therapy, compared with tumours treated with photodynamic therapy alone but using twice the light dose (Baas et al, 1996).…”
Section: Discussionmentioning
confidence: 55%
“…The same authors have also treated four patients with breast metastases to the skin. They were able to achieve similar responses in those tumours treated with MMC followed by photodynamic therapy, compared with tumours treated with photodynamic therapy alone but using twice the light dose (Baas et al, 1996).…”
Section: Discussionmentioning
confidence: 55%
“…These marked fluctuations in PDT sensitivity with growth rate may account for the wide scatter observed in our measurements of clonogenic cell survival following PDT. Mitomycin C has been demonstrated to potentiate photodynamic therapy both at the cellular level (Ma et al, 1992a(Ma et al, , 1993aDatta et al, 1997) and in vivo (Baas et al, 1994(Baas et al, , 1996. This potentiation of PDT is associated with a mitomycin-C induced cell cycle arrest in late S-phase/G2 (Ma et al, 1992b).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic radiosensitizers, such as mizonidazole, which substitutes for oxygen in accepting radicals, have enhanced cancer cure rates (Hirsch et al, 1987). Concommitant use of chemotherapeutic agents that target hypoxic cells, such as mitomycin C, which is selectively metabolized to toxic intermediates by hypoxic cells, have also shown promise (Baas et al, 1996). Another potent bioreductive drug, tirapazamine (SR 4233), is currently undergoing clinical trials and may be used as an adjunct to PDT, although initial in vivo studies have only shown a slight improvement in survival with this agent (Baas et al, 1993).…”
Section: Control Survivalmentioning
confidence: 99%